(untitled) (JBN (Jurnal Bedah Nasional), 2026)
Aim: This systematic review aims to determine whether preoperative saphenous vein diameter influence the success rate outcomes of endovenous laser ablation (EVLA) in patient with varicose veins. Methods: A Systematic Review with a comprehensive search for articles published in the last decade was performed on ScienceDirect and PubMed. After screening process, three high quality studies about the correlation between preoperative saphenous vein diameter and outcomes of EVLA procedure success were identified on inclusion criteria. The Newcastle-Ottawa Scale (NOS) was employed to assess the quality. Results: The larger diameter of saphenous vein is an independent risk factor predictor of technical failure, as consistently demonstrated by the synthesis of the included studies (n=3). Veins measuring greater than 12 mm in was associated with a higher incidence of partial recanalization compared with smaller diameter veins. According to the research’s review that EVLA is effective but the effectiveness depends largely on the energy-to-diameter ratio. To achieve sustained fibrotic occlusion, larger veins need a higher Linear Endovenous Energy Density (LEED). Conclusion: The diameter of the saphenous vein is a key predictor of EVLA performance. While a larger diameters are linked to an increased risk of recanalization, tailored procedural strategies such as a higher energy delivery, optimized tumescent compression and the use of advanced laser technologies may improve outcomes. Accurate preoperative measurement of vein diameter is essential for patient selection and personalize treatment planning.